Current Challenges and Potential Solutions for Targeted Drug Delivery (TDD) in Cancer Pain Management - Chung M; Kalia H; Schatman ME; Robinson CL (Journal of Pain Research)
Matthew Chung,1 Hemant Kalia,2 Michael E Schatman,3,4 Christopher L Robinson5 1Department of Pain Medicine, Division of Anesthesia, Critical Care and Pain Medicine, The University of Texas MD Anderson Cancer Center, Houston, TX, USA; 2Center for Research and Innovation in Spine and Pain (C.R.I.S.P.), Rochester, NY, USA; 3Department of Anesthesiology, Perioperative Care, and Pain Medicine, NYU Grossman School of Medicine, New York, NY, USA; 4Department of Population Health-Division of Medical Ethics, NYU Grossman School of Medicine, New York, NY, USA; 5Department of Anesthesiology, Perioperative, and Pain Medicine, Harvard Medical School, Brigham and Women’s Hospital, Boston, MA, USACorrespondence: Matthew Chung, The University of Texas MD Anderson Cancer Center, 1400 holcombe Boulevard, Unit 409, Houston, TX, 77030, USA, Email mchung1@mdanderson.org